Modern weapons and military equipment for issue 2/2014 - Ostojić, Nikola M. (Vojnotehnički glasnik / Military Technical Courier, 2014)
Armed with motorcycles as a relic of history, or ... Laser sight with 850 nanometer wavelength Microsoft "kinekt" on the Korean border guards Smart gun IDF buying aircraft "osprej"